Treating University Students' Depression using Physical Activity with Peers: Two Field-Based Quasi-Experiments Grounded in the Self-Determination Theory. Issue 3 (3rd July 2021) - Keeler, L. A.; Skidmore, B.; Leenstra, T.; MacDonald, J. R.; Stewart, D.
ABSTRACT: The present research aimed to test the effectiveness of peer-supported, physical activity (PA) intervention for university students with depression. The 8–10 week intervention was structured to fulfill the basic psychological needs (BSN) of competence, autonomy, and relatedness outlined in the self-determination theory. Two studies were completed in subsequent years. In Study 1, ten students participated. Large effect size improvements were found in PA levels, BSN for PA, and depression scores. Inductive analysis of written feedback indicated evidence and examples of psychological need fulfillment. In Study 2, thirteen participants were compared to a matched-paired control group. Using a MANOVA, there was an interaction effect between group and time on the combined dependent variables. The intervention group had improvements to their depression and distress scores; the control group did not. Overall, a peer-based, PA intervention targeting BSN appears to be effective at decreasing depression and distress scores in students with depression.